Effectiveness of the Fiocruz recombinant ChadOx1-nCoV19 against variants of SARS-CoV-2 in the Municipality of Botucatu-SP - Costa Clemens, Sue Ann; Fortaleza, Carlos Magno Castelo Branco; Crowe, Madeleine; Tasca, Karen Ingrid; Spadaro, André Gasparini; Souza-Neto, Jayme Augusto; Grotto, Rejane Maria Tommasini; Sider, Regina; Jimeno, Jose; Verstraeten, Thomas; Clemens, Ralf (Frontiers in Public Health, 2022)
Introduction As the COVID-19 pandemic progresses, rapidly emerging variants of concern raise fears that currently licensed vaccines may have reduced effectiveness against these new strains. In the municipality of Botucatu, São Paulo State, Brazil, a mass vaccination campaign using ChadOx1-nCoV19 was initiated on 16th of May 2021, targeting people 18–60 years old. Two vaccine doses were offered 12 weeks apart, with the second delivered on 8th of August, 2021. This setting offered a unique opportunity to assess the effectiveness of two ChadOx1-nCoV19 doses in a real-life setting. Materials and methods Data on testing, hospitalization, symptoms, demographics, and vaccination were obtained from the Hospital das Clínicas da Faculdade de Medicina de Botucatu. A test-negative study design was employed; whereby the odds of being vaccinated among cases vs controls were calculated to estimate vaccine effectiveness (VE; 1-OR). All individuals aged 18–60 who received a PCR test after the 16th of May and were unvaccinated prior to this date were included in the analysis until the study ended in mid-November 2021. Results 77,683 citizens of Botucatu aged 18–60 received the first dose, and 74,051 received a second ChadOx1-nCoV19 dose 12 weeks later for a vaccination coverage of 84.2 and 80.2%, respectively. Of 7.958 eligible PCR tests, 2.109 were positive and 5.849 negative. The VE against any symptomatic infection was estimated at 39.2%, 21 days after dose 1, and 74.5%, 14 days after dose 2. There were no COVID-19-related hospitalizations or deaths among the 74,051 fully vaccinated individuals. The VE against severe disease was estimated at 70.8 and 100% after doses 1 and 2, respectively. 90.5% of all lineages sequenced between doses 1 and 2 (16th of May−7th of August) were of the Gamma variant, while 83.0% were of the Delta variant during the second period after dose 2 (8th of August−18th of November). Discussion This observational study found the effectiveness of ChadOx1-nCoV19 to be 74.5% against COVID-19 disease of any severity, comparable to the efficacy observed in clinical trials (81.3% after dose 2), despite the dominance of the Gamma and Delta VoCs. No COVID-19-related hospitalizations or deaths in fully vaccinated individuals were reported.